2013
DOI: 10.1155/2013/125936
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modeling and Validation on a New Valve Core of the Throttle Valve in MPD

Abstract: To achieve different demands for pressure control in managed pressure drilling (MPD), the relationship between the pressure difference and the valve opening was analyzed in the working process of MPD throttle. The throttle flow area equation and the flow area isosurface equation at different openings were derived. Then, the mathematical model of the throttle valve surface shape was established by solving the envelope curve of isosurface cluster. Furthermore, the shape curve equation of the valve core surface w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In addition, the output values of the displacement sensor, pressure sensors, and flowmeter remain stable within an accuracy of 0.1 mm, 0.2 Mpa, and 0.5 m 3 /h, respectively; that is to say, the obtained data completely meet the accuracy requirements after being periodically filtered and averaged. On the other hand, the actual fluid density is determined to be 1682 ± 5% kg/m 3 , slightly smaller than that used in the theoretical design in Fu's study (1700 kg/m 3 ) [13]. As previously mentioned, five groups of recorded data, including the import pressure ( IM ), export pressure ( EX ),…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition, the output values of the displacement sensor, pressure sensors, and flowmeter remain stable within an accuracy of 0.1 mm, 0.2 Mpa, and 0.5 m 3 /h, respectively; that is to say, the obtained data completely meet the accuracy requirements after being periodically filtered and averaged. On the other hand, the actual fluid density is determined to be 1682 ± 5% kg/m 3 , slightly smaller than that used in the theoretical design in Fu's study (1700 kg/m 3 ) [13]. As previously mentioned, five groups of recorded data, including the import pressure ( IM ), export pressure ( EX ),…”
Section: Resultsmentioning
confidence: 79%
“…Based on the achievements in Fu's study [13], the design parameters of the new valve cores are shown in Table 1. The theoretical profile curve of the new valve core, which meets linear − Δ relationship, is shown in Figure 2.…”
Section: New Valve Core Proposing Improvement In Prior Workmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the erosion resistance evaluation of the three common throttle valves basically stops at the stage of finiteelement analysis for fluid flow field simulation [3][4][5][6][7]. The previous analysis on the flow field of throttle valve reveals that the mud flow peaks in the axial direction of the plug of the wedge valve, and the wedge surface is extremely prone to erosion under the impact of mud.…”
Section: Introductionmentioning
confidence: 99%
“…However, interference is found usually at the sealing surface, which results in leakage and extra friction. To avoid all these problems, optimized design of structure, especially for the sealing surfaces, is required before precise manufacturing [16,17]. Until now, several researches have been carried out to discuss the optimization strategies for the design of butterfly valve.…”
Section: Introductionmentioning
confidence: 99%